2015
DOI: 10.17062/cjil.v1i2.13
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transformational Leadership and Organizational Commitment in Nonprofit Long Term Care Organizations: The Direct Care Worker Perspective

Abstract: Abstract. The United States population is rapidly aging, and retaining direct care workers (DCWs) will continue to be a workforce concern for the industry in addressing the demand for long term care services. To date, scant literature exists that addresses the DCW perspective of leadership behaviors and their influence on organizational commitment. To respond to this deficiency, this research studied leadership behaviors of direct importance for DCWs at the immediate supervisor level, and provided empirical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
(69 reference statements)
2
19
0
2
Order By: Relevance
“…Moreover, the result of this research supports Kim and Kim (2014) It can be concluded that one of the novel contributions of this research relates to the influence of transformational leadership dimensions on employees' organizational commitment dimensions which have not been adequately and empirically investigated, as is evident in the literature (Meyer et al, 2002;So, 2009). This is particularly so with respect to the non-profit organizations generally (Freeborough, 2012;Porter, 2015), and specifically for Omani public service organizations (S. A. Khan, 2010).…”
Section: Conclussupporting
confidence: 53%
“…Moreover, the result of this research supports Kim and Kim (2014) It can be concluded that one of the novel contributions of this research relates to the influence of transformational leadership dimensions on employees' organizational commitment dimensions which have not been adequately and empirically investigated, as is evident in the literature (Meyer et al, 2002;So, 2009). This is particularly so with respect to the non-profit organizations generally (Freeborough, 2012;Porter, 2015), and specifically for Omani public service organizations (S. A. Khan, 2010).…”
Section: Conclussupporting
confidence: 53%
“…Through motivation, a change process happens and subordinates become encouraged and are enthusiastic in achieving organizational goals and objectives (Foon, 2016). From another point of view, transformational leadership is generally defined as a process whereby leaders take conscious action to develop followers into leaders, exhibit behaviors that elicit trust, display selfsacrificial perspectives to build commitment and influence, and demonstrate a moral compass towards mission and purpose ( Porter, 2015). Transformational leaders are often highly visible and known for their passion and energy in all aspects of their work.…”
Section: Introductionmentioning
confidence: 99%
“…Transformational leaders can increase their followers' commitment by providing inspiration, encouraging followers' involvement in work, and supporting followers' self-development (Avolio et al, 2004). Porter (2015) found that transformational leadership has effect on organizational commitment. In addition, McMurray, Pirola-Merlo, Sarros, & Islam (2010) in employees working in Social Enterprise shows that transformational leadership positively affects organizational commitment.…”
Section: Literature Review 21 the Relationship Between Transformatiomentioning
confidence: 99%